Visualization of anatomical structures in the fetlock region of the horse using cone beam computed tomography in comparison with conventional multidetector computed tomography - Bierau, Jonathan; Cruz, Antonio M.; Koch, Christoph; Manso-Diaz, Gabriel; Büttner, Kathrin; Staszyk, Carsten; Röcken, Michael (Frontiers in Veterinary Science, 2024)
Only minor differences between CBCT and MDCT were identified concerning the diagnostic quality of images for osseous structures. Soft tissue structures were better evaluated on MDCT images. In CBCT as well as in MDCT articular cartilage could only be visualized after intraarticular injection of contrast medium.CBCT of the fetlock is a useful and reliable diagnostic tool when evaluating osseous structures and delineating articular cartilage with contrast medium. However, this modality is limited for assessing soft tissues structures.